Risk Management And Policy Of B3* Wastes From Natural Gas Industry In Indonesia - D. A. Ismukurnianto (Scientific Contributions Oil and Gas, 1998)
The main natural gas industry activities that may produce by-product or wastes are exploration, production, storage, gathering, processing, transmission, distribution or some combination of these. Compressor station, for example, generates various types and quantities of waste, which must be managed responsibly, in a manner that does not threaten human health or the environment.It is helpful to identify types and quantities of waste produced, especially hazardous and toxic material (B3), in order to determine waste disposal options and to prepare management procedures in advance of waste being generated. In order side, regulatory body has provided some regulations regarding hazardous and toxic waste management. Finally, it is important to evaluate the risk of hazardous and toxic wastes in order to provide waste management policy. These topics will be discussed in detail in this paper.